Development of Web-Based Interactive Learning Media for Computer Networking Learning - Sekar Wangi Qurrota Aini; Ahmad Kholiqul Amin; Muhammad Rinov Cuhanazriansyah (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2026)
The rapid development of digital technology has encouraged the integration of interactive learning media to improve students' understanding of abstract concepts. This study aimed to develop a web-based interactive learning media for Computer Networking subjects and evaluate its validity, practicality, and effectiveness in improving students' conceptual understanding. The study employed the Research and Development (R&D) method using the Four-D (4D) model, consisting of Define, Design, Develop, and Disseminate stages. The participants included one material expert, one media expert, one vocational school teacher, and 30 tenth-grade students of SMK Al-Muhammad Cepu. Data were collected through observations, interviews, validation sheets, practicality questionnaires, and pretest-posttest assessments. The developed learning media integrates digital learning materials, instructional videos, interactive quizzes, automatic scoring, and learning progress reports within a web-based platform. The validation results indicated that the media achieved an average score of 4.38 from the media expert and 4.50 from the material expert, both categorized as highly valid. Practicality assessment showed excellent results, with teacher and student responses reaching 100% and 88.4%, respectively. Furthermore, the effectiveness test produced an N-Gain score of 0.91, indicating a high improvement in students' conceptual understanding. These findings demonstrate that the developed web-based interactive learning media is valid, practical, and effective for supporting Computer Networking learning in vocational high schools.